In vivo applications and toxicities of AAV-based gene therapies in rare diseases - Qian Zhao; Huifang Peng; Yujin Ma; Huijun Yuan; Hongwei Jiang (Orphanet Journal of Rare Diseases)
Abstract Adeno-associated virus (AAV), renowned for its exceptionally low pathogenicity and significant efficacy in clinical gene therapy, has emerged as a leading delivery vector in the field of gene therapy. AAV can achieve stable gene expression in various tissues, which has made it a promising treatment for genetic disorders. To date, eight AAV-based gene therapies have been approved by the U.S. Food and Drug Administration (FDA) and European Medicines Agency (EMA). This review summarizes clinical trials of AAV gene therapies for rare diseases, including ophthalmic diseases, nervous system disorders, hematological diseases, neuromuscular diseases, lysosomal storage diseases. We also explore potential side effects and toxicities associated with AAV therapies. Our objective is to provide valuable insights for researchers and clinicians working on AAV-based therapies, helping improve the safety and effectiveness of these treatments.